Caregiving during the COVID-19 pandemic: the new challenge in oncology assistance? - Crocetti, Sonia; Ballatore, Zelmira; Scortichini, Laura; Giglio, Enrica; Merloni, Filippo; Ranallo, Nicoletta; Del Prete, Michela; Catalano, Vincenzo; Safi, Mobin; Battelli, Nicola; Mariotti, Lorenzo; Catani, Claudia; et al. (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The coronavirus disease 2019 (COVID-19) pandemic led to significant restrictions regarding cancer patients, who are considered vulnerable. The aim of our study is to evaluate COVID-19’s impact on oncological caregiving. Methods: Between February and April 2021, we submitted a survey to caregivers of patients who were undergoing active treatment regarding their perception of patient safety and continuity of care in 6 Oncology Departments (OD) in the Marche region. We also conducted Zarit Burden Interview (ZBI) to evaluate the burden placed on caregivers. Results: 112 caregivers responded to our survey and the majority of which declared to have increased assistance time. Furthermore, caregivers over 45 years of age did not experience statistically significant worse economic effects (p=0.04). All caregivers asserted that OD complied with safety recommendations to limit virus spread. Although 86 (76.8%) confirmed that hospital accesses had been restricted, only 10 (8.9%) perceived these precautions to be too restrictive. Approximately all respondents declared they had effective communication with healthcare providers and more than half perceived that quality of care had not been affected by the pandemic. According to ZBI scores, 46 caregivers (41.1%) had a mild to moderate burden level. Conclusions: Our survey underlined the negative effect of COVID-19 on cancer patients’ caregivers, although cancer care was not perceived to have worsened owing to the pandemic, contrary to previous literature.